Perbandingan Isometric Handgrip Exercise dan Jalan Kaki Terhadap Tekanan Darah Sistolik dan Tekanan Darah Diastolik Pada Pasien Hipertensi - Erni Rahmawati; Arlina Dewi; Novita Kurnia Sari (Jurnal Keperawatan Notokusumo, 2018)
Background: Isometric handgrip exercise is an alternative to decrease blood pressure using handgrip performed with static exercise on contracting muscles, without any changes in muscle length or joint movement. Objective: The research objective to know the comparison of isometric handgrip exercise and walking towards to systolic and diastolic blood pressure to patient with hypertension. Method: This research was quasi experiment design, divided into two intervention groups A (isometric handgrip exercise and walking) and intervention B (walking). The subjects of the study were patients with primary hypertension with the number of each intervention group as many as 22 respondents, so there were 44 respondents totally. Data were collected using simple random sampling where all the patients, with hypertension who lived in the work area of Community Health Center Pohjarak. then analyzed using wilcoxon and Mann-Withney tests on dependent variable. Results: The analysis results of difference in the intervention groups A and B towards decreasing blood pressure, showed that the systolic blood pressure was obtained p value 0.026, indicating that there was difference, whereas the diastolic blood pressure was obtained p value 0.031, indicating that there was difference. Conclusion: Implementation of isometric handgrip exercise and walking can decrease systolic and diastolic blood pressure to patients without hypertention.